Perovskitas contendo lantânio, ferro e cobalto - melhoramento de propriedades texturais via síntese por nanomoldagem e avaliação como catalisadores na redução de NO com CO - Lima, Rita Karolinny Chaves de (Universidade Federal de São Carlos, 2008)
Mixed oxides with perovskite structure have high potential as catalysts in gas depollution processes and particularly in the abatement of nitrogen oxides (NOx). Such solids could be considered as a promising alternative for the replacement of noble metals based catalysts, whose use is predominant. Great flexibility of composition, easy synthesis, low cost and high thermal stability justify the special interest in these materials. However, the low specific surface areas (<10 m2/g) of these solids, when prepared by conventional methods, limit your use in catalytic processes. Some efforts have been made in order to overcome that disadvantage. Nevertheless, the preparation of high surface area ternary or multinary oxides is not easy once their synthesis is associated with solid state reactions carried out at high temperatures. Considering the discussed context, perovskites were obtained in this work by means of a conventional method or via sequencial nanocasting. In the first case, perovskites with LaFe1-xCoxO3 (x = 0, 0.2, 0.3, 0.4, 0.5 and 1) nominal compositions were prepared using the citrate method and nitrate salts as inorganic precursors. In the second case, LaFeO3 and LaFe0.6Co0.4O3 perovskites were obtained by nanocasting using Fluka 05120 activated carbon, Black Pearls 2000 black carbon (Cabot Corporation), and porous carbons nanocasted in Aerosil 200 pyrogenic silica and sílica-SBA-15 mesoporous molecular sieve. X-ray diffraction (XRD), N2 sorption measurements, X-ray fluorescence (XRF), hydrogen temperature programmed reduction (H2-TPR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transformed infrared spectroscopy (FTIR) and thermogravimetry (TG) were used to characterize the studied solids. The catalytic activity of the prepared perovskites was evaluated in the reduction of NO to N2 with CO and in the oxidation of the latter compound to CO2. According to the obtained results, it was evident that in comparison with the conventional route, the nanocasting technique using carbons as hard template was efficient to obtain the pure perovskite phase with specific surface areas substantially higher (25 a 49 m2/g). The prepared perovskites were highly active and selective in the reduction of NO to N2 with CO, as well as in the oxidation of the latter compound to CO2. The most active samples were those whose B sites contain up to about 30 % Co. However, the activity of these catalysts decreases strongly with the presence of O2 or water steam. The La-Fe nanocasted binary perovskites showed, in the studied reactions, remarkable higher catalytic activity than the perovskite with the same composition prepared using the conventional method. The higher activity of these materials was related with the increase of their specific surface area. The nanocasted ternary perovskites with LaFe0.6Co0.4O3 composition, despite of the significant increase in their specific surface area, did not show a considerable increase in their activity. This result is in agreement with the behaviour of La-Fe-Co ternary perovskites, in which Co occupies a proportion of B sites greater than 30 %.
Keywords: Óxidos mistos; Nanopartículas; Área superficial específica; Redução de NO com CO; Perovskitas; Oxidação de CO; Nanomoldagem; Perovskites; Specific surface area; Carbons; Nanocasting; NO reduction; CO oxidation; ENGENHARIAS::ENGENHARIA QUIMICA